Planar polarization of Drosophila and vertebrate epithelia. - Eaton, S. (Current Opinion in Cell Biology, 1997)
Our understanding of the actin and microtubule rearrangements that generate planar polarity in Drosophila and in vertebrate epithelia has been extended by recent discoveries. Three different Rho family proteins have been shown to mediate polarization in the wing and the eye of Drosophila. In vertebrates, the importance of myosin VIIa has been uncovered by mutations that cause defects in planar polarization in the ear. Advances in our understanding of the Frizzled pathway, which coordinates planar polarization in Drosophila, are moving the field closer to understanding the links between signal transduction and polarized cytoskeletal reorganization.